2013
DOI: 10.2478/s11534-012-0155-3
|View full text |Cite
|
Sign up to set email alerts
|

Factorization in the model of unstable particles with continuous masses

Abstract: Abstract:We study processes with unstable particles in intermediate time-like states. It is shown that the amplitudes squared of such processes factor exactly in the framework of the model of unstable particles with continuous masses. Decay widths and cross sections can then be represented in a universal factorized form for an arbitrary set of interacting particles. This exact factorization is caused by specific structure of propagators in the model. We formulate the factorization method and perform a phenomen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The useful procedure to calculate the cross section with a suitable accuracy is the method of factorization [99]; this approach is simple and for the cross section estimation it suggests a clear recipe:…”
Section: Physics and Cosmology Of Hypercolor Su(4) And Su(6) Modelsmentioning
confidence: 99%
“…The useful procedure to calculate the cross section with a suitable accuracy is the method of factorization [99]; this approach is simple and for the cross section estimation it suggests a clear recipe:…”
Section: Physics and Cosmology Of Hypercolor Su(4) And Su(6) Modelsmentioning
confidence: 99%
“…We, however, found that these diagrams present dominant tree level part of cosmic particles scattering cross section off the DM. To calculate total width of the process with the final state B 0 e − νν orπ 0 e − νν, we have used factorization method [118,119] considering independently amplitudes squared of subprocesses with intermediate W and Z-bosons and then estimating the (negative) interference of these contributions. The approach allows us to estimate with reasonable accuracy (no worse than ∼10% due to approximate estimation of the interference) the cross section of an "averaged" process where the final electron and neutrinos are produced by different vertices, W → lν l and Z → ν lνl , which practically coincide for the massless leptons.…”
Section: Uhecr Interaction With Dark Mattermentioning
confidence: 99%
“…Now, there are final states with Br(π 0 ν e µ ν µ ) ≈ 0.99 and Br(π 0 ν e e ν e ) ≈ 10 −2 . These results are justified in the framework of the factorization approach [37].…”
Section: Cosmic Lepton Scattering Off Dark Mattermentioning
confidence: 71%
“…We have found, these diagrams give dominant tree level part of cosmic particles scattering cross section, and we do not take into account small contributions from H-quark loops, hhZ and other multi-scalar vertices [36]. To calculate total cross section of the process with final state B 0 e − ν ν or π0 e − ν ν, it was used factorization method [37] considering independently amplitudes squared of subprocesses with intermediate W and Z-bosons and then estimating the (negative) interference of these contributions. The approach allows to estimate with reasonable accuracy (no worse than ∼ 10% due to approximate estimation of the interference) cross section of an "averaged" process where final electron and neutrinos are produced by different vertices, W → lν l and Z → ν l νl .…”
Section: Cosmic Lepton Scattering Off Dark Mattermentioning
confidence: 99%